2022
DOI: 10.3390/antibiotics11121762
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in Microbiota-Mediated Intestinal Metabolites and Immune Responses Induced by Different Antibiotics

Abstract: The cocktails of antibiotics are utilized to study the functions of microbiota. There have been studies on the alteration of not only the microbiota composition but also the host’s metabolism or immunity. However, the bacterial species associated with these altered physiologic markers are still unclear. Therefore, we supplied mice with drinking water containing ampicillin (AMP), vancomycin (VAN), neomycin (NEO), or metronidazole (MET) to observe the effect of each antibiotic on helper T cells and inflammation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For example, in vitro studies revealed that gentamicin, a first-line antibiotic drug of choice for neonatal sepsis, can directly inhibit the chemotactic response of human polymorphonuclear leukocytes ( 99 ). In another study, mice given Ampicillin or Vancomycin, two other antibiotics commonly used in neonates, exhibited significant downregulation of Th17-related genes in the ileum ( 100 ). In the piglet model of NEC, 5 days of antibiotic treatment resulted in significant downregulation of genes related to inflammation and innate immune response following compared to controls ( 45 ).…”
Section: Additional Speculations From Human and Animal Studiesmentioning
confidence: 99%
“…For example, in vitro studies revealed that gentamicin, a first-line antibiotic drug of choice for neonatal sepsis, can directly inhibit the chemotactic response of human polymorphonuclear leukocytes ( 99 ). In another study, mice given Ampicillin or Vancomycin, two other antibiotics commonly used in neonates, exhibited significant downregulation of Th17-related genes in the ileum ( 100 ). In the piglet model of NEC, 5 days of antibiotic treatment resulted in significant downregulation of genes related to inflammation and innate immune response following compared to controls ( 45 ).…”
Section: Additional Speculations From Human and Animal Studiesmentioning
confidence: 99%
“…These changes were associated with improvements in baseline insulin values and insulin resistance in overweight and obese adults [ 143 ]. All three metabolites (TMAO, choline, and L-carnitine) have been associated with diabetes and gut-microbiota activity [ 144 , 145 ].…”
Section: Gut Barriers and Metabolic Disordersmentioning
confidence: 99%